Bioprospecting Indigenous Marine Microalgae for Polyunsaturated Fatty Acids Under Different Media Conditions - Jain, Priyanshu; Minhas, Amritpreet Kaur; Shukla, Sadhana; Puri, Munish; Barrow, Colin J.; Mandal, Shovon (Frontiers in Bioengineering and Biotechnology, 2022)
Marine microalgae have the potential to produce a number of valuable compounds which have a significant role in the pharmaceuticals, biomedical, nutraceutical, and food industries. Although there are numerous microalgal germplasms available in the marine ecosystem, only limited strains were recognized for their commercial potential. In this study, several indigenous microalgal strains were isolated from the coast of the Arabian Sea for exploring high-value compounds like polyunsaturated fatty acids (PUFA). Based on the high PUFA contents, two isolated strains were identified using 18S rDNA sequencing and selected for further studies to enhance PUFA. From the molecular analysis, we found both the strains were green microalgae, one of them belonged to Chlorella sp. while the other was Planophila sp. Along with the two strains, Nannochloropsis oculata, known for high yielding PUFA, were grown in 3 different nutrient media for PUFA augmentation. The relative content of α-Linolenic acid (ALA) contents in fatty acids reached a maximum of up to 50, 36, and 50% respectively in Chlorella sp., Planophila sp., and N. oculata. To our knowledge, this is the first study in exploring fatty acids in Planophilla sp. Our results showed a higher PUFA content, especially α-Linolenic acid at low nutrients in media